R. W. Mountjoy, John Hartman, Ralph Wilkerson, and Harry Lineback turning on the Christmas lights in downtown Winston-Salem, 1959. - (:unkn) unknown (Forsyth County Public Library, 2009)
WSJ 11-28-59 p.1.
R. W. Mountjoy, John Hartman, Ralph Wilkerson, and Harry Lineback turning on the Christmas lights in downtown Winston-Salem, 1959.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth